Evaluation of immunostimulatory effects of a commercial herbal extract on avian influenza subtype H9N2 and Newcastle disease vaccination in chickens - Talazadeh, Forough; Mayahi, M; Fathi, M (Journal of the Hellenic Veterinary Medical Society, 2022)
Contrary to several vaccination programs to protect against bird flu and Newcastle disease (ND), these diseases remain a significant threat to the poultry industry. Improving the immune responses is important for many reasons such as vaccine failure, immunosuppressive diseases, and antibiotics misuse. Nowadays, research on materials likely to have immune-enhancing effects is increasing. Factors, substances, or compounds that can regulate different functions of the immune system can be used to enhance specific and even nonspecific responses to vaccines. The ability of herbal extracts to improve the immune system supports their use as immune stimulants. The present study aimed to examine the effects of barley malt extract in drinking water on humoral immunity of broiler chickens against ND and Avian Influenza (AI) disease subtype H9N2 vaccines. A total of 225 one-day-old broiler chicks (Ross strain) were divided into 5 groups of 3 subgroups and each subgroup had 15 chicks. Group A, B, and C chickens received 0.2%, 0.3%, and 0.5% of malt extract respectively in drinking water. Group D chickens did not get malt extract. Group E chickens did not receive malt extract and Newcastle and AI vaccines as the control group. All groups except group E were vaccinated with live Newcastle vaccine (B1 strain) intraocularly and AI-ND subtype H9N2 killed vaccine subcutaneously on the 7th day. Antibody titer against NDs and AI vaccines was considered by the Hemagglutination Inhibition test (HI test). Malt extract at 0.5% concentration, at all periods after vaccination, enhanced the systemic antibody response to ND vaccine in broiler chickens, but this extract had no significant effect on antibody response against the AI vaccine. Conclusion: Inoculation of ND vaccines with barley malt extract as an immune-boosting agent induces extensive immune responses involved in HI-NDV Ab titers.